Urgensi Ilmu Ushul Fiqih dalam Istinbath Hukum Islam - Rikardo, Riki; Sucipto, Imam (TSAQOFAH, 2026)
The science of usul al-fiqh is a fundamental discipline in Islamic legal studies that functions as a standard methodology for the process of legal derivation (istinbat) from the sources of the shari‘ah. Without mastery of this discipline, legal rulings risk becoming subjective, partial, and inconsistent with the objectives of the law (maqasid al-shari‘ah). This article aims to examine the urgency of usul al-fiqh in the istinbat of Islamic law, both theoretically and applicatively, particularly in responding to contemporary issues. The method used is library research with a descriptive–analytical approach to classical and contemporary works on usul al-fiqh. The findings show that usul al-fiqh plays a crucial role in safeguarding the authority of legal evidences, ensuring methodological consistency, and maintaining the relevance of Islamic law across time and space through a systematic and accountable framework of ijtihad. Thus, strengthening the study of usul al-fiqh is indispensable for the development of Islamic law that is moderate, adaptive, and grounded in sound evidences, while also supporting the realization of maqasid al-shari‘ah in an ever-changing social context.